The invasive barnacle species, Austrominius modestus: Its status and competition with indigenous barnacles on the Isle of Cumbrae, Scotland. (5th January 2015) - Gallagher, Mary Catherine; Davenport, John; Gregory, Susan; McAllen, Rob; O'Riordan, Ruth
Abstract: The invasive barnacle Austrominius (= Elminius) modestus has been present in Europe since the 1940s, and has recently been recorded to outnumber native barnacle species at some locations, including an Irish marine nature reserve. It has been suggested that these increases in abundance following a lag phase since establishment, represent the awakening of an 'ecological sleeper', due to changes in environmental conditions. Austrominius modestus was first recorded on the Isle of Cumbrae, Scotland in 1955, and was reported to be well established on the island by 2007. Since this location is close to the northern limit of the invaded range of A. modestus, it has been chosen as a site for the long term monitoring of this species. Quantitative and semi-quantitative surveys of the abundance of A. modestus, together with the native barnacle species Chthamalus montagui and Semibalanus balanoides, have been made on the island on a biannual basis since 2009. This study examined changes in the abundances of these three species from 2009 to 2013, and reports on the present status of this invasive species on the island. Austrominius modestus was found at all sites surveyed, but did not outnumber native barnacle species at any site. Semibalanus balanoides, a cold water boreal species, was the most abundant barnacle species at most sites from 2009 to 2013. All three barnacle species underwent a decline in 2011, but had increased in abundance by 2013. Despite undergoing the smallest increase in abundance between 2011 and 2013, S. balanoides remains the dominant barnacle species on the Isle of Cumbrae. Nearly sixty years after its initial discovery on the island, A. modestus is widespread, however it has not outnumbered native species, which continue to recruit at high densities. This competitive pressure makes it unlikely that A. modestus will outnumber native barnacle species at this location, close to its northern limit, in the near future.